No Increase in Frequency of Antifungal Resistance among Yeasts Isolated from Normally Sterile Sites in Patients at Foothills Hospital from 1993 to 1996 - A Patrick Gibb; Cheryl Thorson; Harry van den Elzen (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the prevalence of resistance to antifungal drugs among yeasts isolated from sterile sites from patients in one hospital and the relationship of resistance to antifungal use, and to assess whether resistance was increasing.